2015
DOI: 10.1039/c4ta06642a
|View full text |Cite
|
Sign up to set email alerts
|

Highly branched cobalt phosphide nanostructures for hydrogen-evolution electrocatalysis

Abstract: CoP nanostructures that exposed predominantly (111) crystal facets were synthesized and evaluated for performance as electrocatalysts for the hydrogen-evolution reaction (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 27 publications
6
89
0
Order By: Relevance
“…[18][19][20][21] This approach has been extensively employed for the synthesis of binary phosphides, and these have recently been demonstrated to be effective as model catalysts for HDS 22,23 as well as electrocatalysts for HER. [6][7][8][9][10] In contrast, few examples of arrested precipitation reactions delivering ternary phosphide nanoparticles are reported. 24,25 Such reports often target a limited range of composition space and do not perform the systematic evaluation needed to control the reaction characteristics to yield targeted size, composition, and shape.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…[18][19][20][21] This approach has been extensively employed for the synthesis of binary phosphides, and these have recently been demonstrated to be effective as model catalysts for HDS 22,23 as well as electrocatalysts for HER. [6][7][8][9][10] In contrast, few examples of arrested precipitation reactions delivering ternary phosphide nanoparticles are reported. 24,25 Such reports often target a limited range of composition space and do not perform the systematic evaluation needed to control the reaction characteristics to yield targeted size, composition, and shape.…”
Section: Introductionmentioning
confidence: 86%
“…4,5 With respect to catalysis, transition metal phosphides are being evaluated for both hydrodesulfurization (HDS) and hydrogen evolution reaction (HER) processes, among others. [6][7][8][9][10][11] While binary phases have been extensively studied, 6,10,12 only recently have researchers started to explore opportunities for synergism afforded by ternary phases. [13][14][15][16] Ternary phosphides of formula Ni 2-x Co x P are of particular interest as they have shown improved HDS activity relative to the best of the binary phases (Ni 2 P) for low concentrations of Co (x ≤ 0.1).…”
Section: Introductionmentioning
confidence: 99%
“…Dismukes et al 137 prepared Ni5P4 crystalline with abundant P element which showed high performance efficiency on par with Pt in strong acid (33 mV dec −1 Tafel slope and −62 mV overpotential at −100 mA cm −2 in 1 M H2SO4). Recently, Lewis et al 139 H2SO4. As shown in Fig.…”
Section: Transition Metal Phosphidesmentioning
confidence: 99%
“…[4] Noble metals, especially platinum, are still regarded as the best electrocatalysts for efficient hydrogen production. [5][6][7][8] However, their limited abundance and high cost have inevitably prevented the practical realization of the dreamed hydrogen economy.Thus, developing earth-abundant, low-cost electrocatalysts with a high catalytic activity in electrochemical hydrogen evolution reaction (HER) is critical in realizing the hydrogen economy to lift our future welfare and civilization.Over the past years, tremendous efforts have been devoted to the exploration of noble metalfree HER catalysts, and great progresses have been achieved with discoveries of highly active earth-abundant transition-metal based materials, such as phosphides, [9][10][11][12][13][14][15] dichalcogenides, [16][17][18][19][20] and Ni-Mo alloys. [21][22][23] Most of these catalysts are stable and/or have high activities in acidic conditions, and only very a few of them possess high and stable activities in alkaline media.…”
mentioning
confidence: 99%
“…Over the past years, tremendous efforts have been devoted to the exploration of noble metalfree HER catalysts, and great progresses have been achieved with discoveries of highly active earth-abundant transition-metal based materials, such as phosphides, [9][10][11][12][13][14][15] dichalcogenides, [16][17][18][19][20] and Ni-Mo alloys. [21][22][23] Most of these catalysts are stable and/or have high activities in acidic conditions, and only very a few of them possess high and stable activities in alkaline media.…”
mentioning
confidence: 99%